2022
DOI: 10.1002/aoc.6798
|View full text |Cite
|
Sign up to set email alerts
|

Pb (II) and Hg (II) thiosemicarbazones for inhibiting the broad‐spectrum pathogen Cladosporium sphaerospermum ASU18 (MK387875) and altering its antioxidant system

Abstract: Pb (II) and Hg (II) ions were reacted in aqueous solution with two tridentate thiosemicarbazones, resulting in four complexes {[Pb(L1)2] 1, [Pb(L2)2] 2, [Hg(L1)2] 3, and [Hg(L2)2] 4; HL1 = 4‐(4‐nitrophenyl)‐1‐[(pyridin‐2‐yl)methylene]thiosemicarbazide and HL2 = 4‐(2‐chlorophenyl)‐1‐[(pyridin‐2‐yl)methylene]thiosemicarbazide}. The solid‐state structures of complexes 2 and 3 were determined by X‐ray crystallography, which also confirmed the monobasic tridentate NNS nature of the ligands, and the octahedral coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…However, HL 2 and C2 gave moderate antibacterial activities slightly higher for the complex against the two bacterial strains, but the activities are still less when compared with the standard. The inactivity of HL 1 and its complex, compared with the activities of HL 2 and C2, is probably due to their higher nitrogen content, as nitrogen is a vital element required for the growth of the microorganisms [42]. Indeed, metal complexes have been reported in several papers as long-acting drugs with slow releases in the cells, and the higher activities given by complexes relative to those of their ligands have been documented in several papers that concluded that upon coordination, the ligands bio-active or -inactive improved their antimicrobial activities or attained some pharmacological action [43,44].…”
Section: Bacterial Inhibitionmentioning
confidence: 99%
“…However, HL 2 and C2 gave moderate antibacterial activities slightly higher for the complex against the two bacterial strains, but the activities are still less when compared with the standard. The inactivity of HL 1 and its complex, compared with the activities of HL 2 and C2, is probably due to their higher nitrogen content, as nitrogen is a vital element required for the growth of the microorganisms [42]. Indeed, metal complexes have been reported in several papers as long-acting drugs with slow releases in the cells, and the higher activities given by complexes relative to those of their ligands have been documented in several papers that concluded that upon coordination, the ligands bio-active or -inactive improved their antimicrobial activities or attained some pharmacological action [43,44].…”
Section: Bacterial Inhibitionmentioning
confidence: 99%